Management of Shweta Pradara (Leucorrhoea) Through Ayurveda- A Case Series (International Journal of Ayurveda and Pharma Research, 2022)
Leucorrhoea or vaginal discharge is generally whitish, yellowish or greenish vaginal discharge in females that might be normal or a symptom of infection. It is almost mucus discharge, which exhibit exfoliation of vaginal epithelial cells due to estrogen influence on the vaginal mucosa. It is important to identify the differences between physiological and pathological discharges. In Ayurveda, leucorrhoea is known as Shweta Pradara, where Shweta means white and Pradara mean discharge. Yoni vyapadas which are caused by Kapha or Vatakaphaja doshas are the main causative factors of Shweta pradara. It also depends on the Nidana which may lead to vitiation of any of the Doshas An attempt was made to manage Shweta pradara by Ayurvedic treatment protocol in dispensary at OPD level. This study was conducted on five unmarried female patients having symptoms of Shweta pradara. These patients came with complaints of vaginal discharge, itching in vaginal area, backache etc., and were treated with Shunthi Dhanyak Siddha Jala for Deepan Pachan, Haritaki churna for Anuloman, Jeevak plus capsule, Gynaevin syrup for oral medication, and Triphala Kwatha for Yoni Prakshalan, Himtone forte as Rasyana and Balya aushadhi. The whole treatment was done for 4 weeks and marked improvement was achieved in all the patients